DECISION SUPPORT SYSTEM IN ASSESSMENT OF EMPLOYEE PERFORMANCE AT MNC GROUP USING SAW (SIMPLE ADDITIVE WEIGHTING) METHOD USING WHITE BOX TESTING - Nur Roqim (Universitas Islam Balitar, 2018)
MNC Group as a television media company, performs performance appraisal for each employee as a job evaluation material, which is carried out by the head of the division, one of which is the head of the technical division of 112 other employees. The process of evaluating employee performance at MNC Group is still done manually, which is using Microsoft Excel applications one by one which makes the length of the process. The employee's assessment and appraisal report does not display the ranking from the top to the bottom of all of the employees. Decision support system in evaluating employee performance in MNC Group using the SAW (Simple Additive Weighting) method with this white box test is made to assist the head of the division to expand employee appraisal capabilities. The employee performance appraisal process is carried out in a computerized, structured and systematic manner based on the assessment criteria previously determined by the MNC Group, namely the quantity of work, accuracy & time management, quality of work and efficiency. The SAW (Simple Additive Weighting) method is a weighted addition method by looking for weighted sums of performance ratings on each alternative on all attributes. So that it can be obtained from every employee at MNC Group. Testing of system results that have been made is very necessary to know that the system is running well. Tests carried out are white box testing which is based on checking the details of the design, using the control structure of the program design procedurally to divide the test into several test cases. So that the value of the test results is known, namely 2 with the type of procedure is a simple procedure and the risk level is low risk.